Time-varying agglomeration economies and aggregate wage growth - Clémence Berson; Pierre-Philippe Combes; Laurent Gobillon; Aurélie Sotura (European Central Bank (ECB), 2024)
We examine how agglomeration economies have influenced labour earnings in France over forty years. First, we define cities dynamically to account for their changing footprints. Our findings show that aggregate wage growth is mainly driven by growth in larger cities, rather than smaller ones or by population shifts across cities. We estimate individual wages incorporating time-varying city and individual fixed effects, and analyse how city characteristics (employment density, area, and market access) and their returns impact wage evolution. Changes in the values of these characteristics have minimal effect, but changes in their returns significantly influence wages, with notable variation across cities. Overall, aggregate wage growth in France reflects larger returns to larger city size. Our model, that incorporate the impact of agglomeration economies on city size and population, suggests that changes in returns do not drive population or area changes sufficiently to impact aggregate labour earnings, supporting our empirical findings.
Keywords: R23; J31; J61; 330; Agglomeration economies; endogenous city size; growth; wages